2019
DOI: 10.1055/s-0039-1691758
|View full text |Cite
|
Sign up to set email alerts
|

Total Endoscopic Transcanal Cartilage Myringoplasty: A Prospective Study

Abstract: Introduction  Middle ear surgeries, including myringoplasty, have increasingly utilized endoscopes as an adjunct to or as a replacement for the operative microscope. Objectives  The objective of the present study was to evaluate the graft uptake rate and to evaluate the hearing results. Methods  This is a prospective study. We have analyzed 139 patients who underwent surgery for chronic otitis media (COM) of the mucosal type. All of the surgeries were performed exclusively under total endoscopic transcanal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The disadvantages of EES include one hand surgery that requires surgical skills. 6,10,11 Bleeding is always the issue, but once the flap is raised, it is not much of the problem even if granulation tissues are present. We had 3 patients who were converted into microscopic ear surgery due to bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disadvantages of EES include one hand surgery that requires surgical skills. 6,10,11 Bleeding is always the issue, but once the flap is raised, it is not much of the problem even if granulation tissues are present. We had 3 patients who were converted into microscopic ear surgery due to bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…10 Endoscopic ear surgery (EES) is a recently introduced field in otology, and many otologists are now accepting it. 11 The endoscope was introduced in the world by Harold Hopkins as Hopkins rod endoscope in 1966. 12 However, the first study on transcanal EES (TEES) was only reported in 1992 by El Guindy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown equivalent or improved results from endoscopic versus microscope-guided tympanic membrane perforation closure and clearance of cholesteatoma in children (8,9). Research suggests that audiometric outcomes are equivalent in experienced hands between TEES and PAM approaches for most common procedures including tympanoplasty, ossiculoplasty, and stapedotomy (3,7,8,(10)(11)(12)(13). Because TEES allows surgeons to complete these procedures with less soft tissue dissection than by a post-auricular approach, examination of secondary patient outcomes related to surgical morbidity may demonstrate a potential benefit of TEES over post-auricular surgery.…”
Section: Objectivementioning
confidence: 99%
“…The endoscope offers a wide and comprehensive transcanal view of all elements of this procedure: the ear canal, tympanic membrane and eardrum, without the need to constantly move the microscope, even with an anterior ridge. (12) Objectives: To clinically assess the postoperative outcomes of endoscopic assisted Trans canal underlay tragal cartilage myringoplasty.…”
Section: Complicationmentioning
confidence: 99%